Relationship Analysis of Corporate Governance Mechanisms, Audit Fees, and Financial Report Quality in Indonesia - Hapsoro, Dody; ., . (International Journal of Engineering and Technology, 2018)
The aim of this study is to examine the effect of corporate governance mechanisms on the financial reporting quality and examine the effect of corporate governance mechanisms on audit fees. In addition, this study also aimed to examine the effect of audit fees on the financial report quality. The sample in this study is manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the period 2014 and 2015. The total sample is 144 companies. Data analysis was performed using Partial Least Squares (PLS). The results of this study show that the proportion of independent commissioners and audit committee from the board of commissioners and audit committee negatively affect audit fees; the proportion of independent commissioners and audit committee from the board of commissioners, audit committee, and board of directors negatively affect audit fees; the proportion of independent commissioners and audit committee from the board of commissioners and audit committee do not positively affect the financial report quality; the proportion of independent commissioners and audit committee from the board of commissioners, audit committee, and board of directors do not positively affect the financial report quality; and audit fees negatively affects the financial report quality.
Keywords: Corporate Governance Mechanisms; Audit fees; Financial Reporting Quality